2022
DOI: 10.1149/1945-7111/ac4cda
|View full text |Cite
|
Sign up to set email alerts
|

Ru-Doped NiFe Layered Double Hydroxide as a Highly Active Electrocatalyst for Oxygen Evolution Reaction

Abstract: Improving the intrinsic catalytic activity of NiFe layered double hydroxide (LDH), which is a benchmark electrocatalyst for oxygen evolution reaction (OER), is a significant challenge. In the present study, we doped ruthenium ions into NiFe LDH (Ru-NiFe LDH) to accelerate the OER kinetics. Electrochemical measurements of NiFe LDH and Ru-NiFe LDH at similar mass loadings showed that Ru-NiFe LDH demonstrated a higher OER activity than that of NiFe LDH. Ru-NiFe LDH only requires an overpotential of 246 mV at 10 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 55 publications
3
17
0
Order By: Relevance
“…At present, the rational design of advanced HER electrocatalysts should consider the two points of the dissociation of water molecules and the H* adsorption energy. Nowadays, the precious metal doping strategy has been widely applied in constructing excellent electrocatalysts in water splitting [ 33 , 34 , 35 ], which can form the optimized catalyst sites with the best free energy profile, thus leading to an ultrahigh mass activity based on precious metals.…”
Section: Heteroatom Doping Strategymentioning
confidence: 99%
“…At present, the rational design of advanced HER electrocatalysts should consider the two points of the dissociation of water molecules and the H* adsorption energy. Nowadays, the precious metal doping strategy has been widely applied in constructing excellent electrocatalysts in water splitting [ 33 , 34 , 35 ], which can form the optimized catalyst sites with the best free energy profile, thus leading to an ultrahigh mass activity based on precious metals.…”
Section: Heteroatom Doping Strategymentioning
confidence: 99%
“…At present, rational design of advanced HER electrocatalysts should consider from two points of the dissociation of water molecules and H* adsorption energy. Nowadays, precious metal doping strategy has been widely applied in constructing excellent electrocatalysts in water splitting [33][34][35], which can form the optimized catalysts sites with a best free energy profile, thus leading to an ultrahigh mass activity-based on precious metals.…”
Section: Precious Metal Dopingmentioning
confidence: 99%
“…An effective approach for conductivity optimization is metal cation doping, which can introduce a new impurity energy level, lower the band gap, reduce the activation energy barriers, and eventually improve the electron density and efficiency of electron transport. 19 Yang et al demonstrated that doping of W, 20 Cr, 21 and Ru 22 metal cations in NiFe layered double hydroxide (NiFe LDH) could enhance the synergistic interplay among multimetallic matrix centers, optimize the intrinsic conductivity, and improve the OER activity. The Sun group incorporated multivalent vanadium (V 5+ , V 4+ , and V 3+ ) into the NiFe LDH lattice to form the trimetallic NiFeV LDH, which exhibited a much higher catalytic activity than pure NiFe LDH for OER.…”
Section: Introductionmentioning
confidence: 99%